The student profile, service delivery model, and support practices of four early childhood intervention environments in Singapore. Issue 3 (2nd July 2016) - Poon, Kenneth K.; Yang, Xueyan
Abstract : The student profile, model of service delivery, and support practices for young children with disabilities receiving early childhood intervention (ECI) in Singapore is reported and contrasted in this study. The supervisors/managers/principals of eight Early Intervention Programme for Infants and Children (EIPIC) centres, eight Integrated Child Care Programmes (ICCP), six privately run ECI centres, and 65 preschools participated in this study. Overall, autism spectrum disorder was the most commonly reported diagnosis in this study. EIPIC and privately run ECI centres supported mostly children with disabilities (frequently those with more severe disabilities) and provided more specialized education and therapy support, whereas ICCPs and preschools educated them alongside typically developing peers. EIPIC centres provided the most resource and teacher support for young children with disabilities. Issues pertaining to the reported rates of disabilities among the young children and support models/practices are discussed.